Pelatihan Pembuatan Minuman Herbal Daun Pecut Kuda di SMA Darul Hikmah Mataram - Rahman, Suburi; Dwiani, Afe; Yuniartini, Ni Luh Putu Sherly; Nugrahani, Rizki; Arini, Laili Azmiati; Patmawati, Patmawati; Salsabila, Riska Dia Salma; Riani, Riani; Maulana, Harpan; Aini, Diah Miftahul (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2024)
SMA Darul Hikmah Mataram is one of the private secondary education institutions in the city of Mataram with the existence of a school that is still beautiful and surrounded by many medicinal plants. The existence of horse whip leaves (Stachytarpheta jamaicensis) in this school is very abundant and still underutilised. Horse whip leaves are useful as antioxidants and anti-inflammatories. Chemical compounds contained in horse whip leaves are flavonoids, terpenoids, alkaloids, tannins, steroids, and saponins. Herbal drinks are one of the practical products that can be processed into antioxidant-rich drinks using very cheap and easy packaging. This activity aims to increase the knowledge of teachers and students at SMA Darul Hikmah Mataram about making drinks, educate and increase the use of horse whip leaves as herbal drinks at SMA Darul Hikmah Mataram, show training participants the processing of horse whip leaves as herbal drinks, and increase product value related to packaging and processing of horse whip leaves as herbal drinks. The methods used were preparation, processing of horse whip leaves into powder, and evaluation. Evaluation is carried out through direct interviews and questions and answers. The results of this service are that the participants follow the entire series of activities well and are able to make pecut kuda herbal drinks in powder form and packaging with pouches, this activity is expected to be a government initiation for the development of local agricultural products in the form of herbs that have high selling value.